Globalization, Sovereignty and Social Unrest - Westaway, Jennifer (Canadian Center of Science and Education, 2012)
The world has seen over recent months an increase in the level of social unrest in response to both the imposition by governments of austerity measures and attempts by civilians to overthrow undemocratic and repressive regimes. This unprecedented and extensive level of unrest across diverse political and economic environments has raised many questions as to the causes and consequences, not the least of which is the challenge to the sovereignty of the state and the role of globalization. This paper will discuss the social unrest consequences of globalization and consider whether globalization has undermined the concept of state sovereignty to such an extent that the social unrest in evidence is in effect the beginning of a new era in international law and international relations.